2018
DOI: 10.7454/hubs.asia.2050418
|View full text |Cite
|
Sign up to set email alerts
|

Guided Act and Feel Indonesia – Internet-based Behavioral Activation Intervention for Depression in Indonesia: A Systematic Cultural Adaptation

Abstract: Depression is one of the leading causes of the global disease burden, affecting millions of people worldwide. The availability of mental health treatment, however, remains very limited in many low-middle income countries, including Indonesia. Internet-based interventions are known to have the potential to deliver mental health treatment economically and appropriately according to numerous studies conducted in high-income countries. In the current study, we describe a systematic cultural adaptation of an intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(37 reference statements)
3
6
1
Order By: Relevance
“…(g) The modules should be kept shorter, which was previously suggested (Abi Ramia et al, 2018; Burchert et al, 2019), and (h) providing a mobile version of the intervention might be a better way to reach refugees (Juniar et al, 2019), given the high use of smartphones compared to desktop computers (Emmer et al, 2016). Furthermore, our participants considered it important (i) to promote the refugees' understanding of western disease- and treatment concepts as well as the healthcare systems, similar to previous findings (Arjadi et al, 2018b; Kizilhan, 2017). (k) This highlights the importance of psychoeducational elements and explanations of exercises and their purposes, in order to bridge diverging explanatory models and to increase the positive expectancy (Gearing et al, 2013; Hinton and Jalal, 2014) as well as trust in the programme, which is shown to be specifically difficult for refugees (Majumder et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…(g) The modules should be kept shorter, which was previously suggested (Abi Ramia et al, 2018; Burchert et al, 2019), and (h) providing a mobile version of the intervention might be a better way to reach refugees (Juniar et al, 2019), given the high use of smartphones compared to desktop computers (Emmer et al, 2016). Furthermore, our participants considered it important (i) to promote the refugees' understanding of western disease- and treatment concepts as well as the healthcare systems, similar to previous findings (Arjadi et al, 2018b; Kizilhan, 2017). (k) This highlights the importance of psychoeducational elements and explanations of exercises and their purposes, in order to bridge diverging explanatory models and to increase the positive expectancy (Gearing et al, 2013; Hinton and Jalal, 2014) as well as trust in the programme, which is shown to be specifically difficult for refugees (Majumder et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Concerning the non-western background, there are several recommended adaptations along with differences in socialisation and everyday habits of refugees. (e) Audio-visual elements should be preferred over text, which corresponds to earlier research (Abi Ramia et al, 2018; Arjadi et al, 2018b; Patel et al, 2017). (f) In order to make the content more understandable (Juniar et al, 2019; Salamanca-Sanabria et al, 2019), language should be held as simple as possible; metaphors and puns should not be used.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study also highlighted that it is important to learn from both providers/experts and users’ perspectives to enhance the applicability of the program and also maintain the therapeutic quality of the intervention. Arjadi and colleagues ( 33 ) applied the Ecological Validity Model to adapt an internet-based behavioral activation intervention addressing depression for Indonesian people. In addition, an internet-based intervention for depression was culturally adapted for Colombian university students using this model ( 34 ) and was evaluated ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews and meta-analyses have summarised studies that conducted IMI in LMIC [53] and investigated the extent and effectiveness of cultural adaptation of IMI for the treatment of common mental disorders among people with diverse cultural backgrounds [48]. Yet, the procedure of the cultural adaptation is often only poorly reported [43,52,[54][55][56]. This makes it difficult to identify components of the cultural adaptation that may contribute to an enhanced acceptance and effectiveness of IMI, such as the language, illustrations, or example characters [43,54,56,57].…”
Section: Introductionmentioning
confidence: 99%